Teologi Pembebasan Dalam Pendidikan Islam Perspektif Asghar Ali Engineer - Dedeh Azizah (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2019)
According to the view of liberation theology, Islamic education must be able to produce people who take a role in the social system that promotes justice as citizens and citizens of the world in the view of religion (just, not oppressed) who are damaged by humans themselves. From the explanation, the author was interested in conducting a study